Music, theology, and space listening as a way of seeking God - England, Frank (2017)
Music, it will be claimed, intones the meaning of being human. In the Christian tradition, music is central to liturgy and worship. From its roots in the New Testament, through its approval or prohibition by the Church Fathers, to the Puritan purges, the Classical liturgical commissions, and the revivalist celebrations, sacred music continues to be a means of negotiating the relationship between human selves and the sacred. The theological importance of music has been examined most recently with respect to time, but the theological promise of the spatial dimension of music either has been ignored or rejected. Accompanied by the Augustine of the Confessions, this article asks whether "the space of music" offers a way of seeking to know who one is and who God is.
Keywords: Music -- Space -- Time -- Cadence -- Self-knowing -- Memory